Schiff Bases and Stereocontrolled Formation of Fused 1,3-Oxazolidines from 1-Amino-2-Indanol: A Systematic Study on Structure and Mechanism - Esther Matamoros; Mark E. Light; Pedro Cintas; Juan C. Palacios (Molecules, 2023)
This paper thoroughly explores the formation of Schiff bases derived from salicylaldehydes and a conformationally restricted amino alcohol (1-amino-2-indanol), as well as the generation of 1,3-oxazolidines, a key heterocyclic core present in numerous bioactive compounds. We provide enough evidences, both experimental-including crystallographic analyses and DFT-based calculations on imine/enamine tautomerism in the solid state and solution. In the course of imine formation, a pentacyclic oxazolidine–oxazine structure could be isolated with complete stereocontrol, whose configuration has been determined by merging theory and experiment. Mechanistic studies reveal that, although oxazolidines can be obtained under kinetic conditions, the prevalence of imines obeys to thermodynamic control as they are the most stable structures. The stereochemical outcome of imine cyclization under acylating conditions leads to formation of 2,4-trans-oxazolidines.